Effects of microbial inoculation, organic and chemical fertilizer on yield and physicochemical and cookability properties of bean (Phaseolus vulgaris L.) seeds - Uyanöz, Refik (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2007)
A field experiment was carried out to study the effects of Rhizobium, Arbuscular mycorrhiza (AM) inoculation, cattle manure and chemical fertilizer on yield, 100-seed weight, total defects and nutrient accumulation of bean {Phaseolus vulgaris L.) seeds. Inoculation and organic fertilizer treatments significantly (p ≤ 0.05) increased yield, 100-seed weight, non-soakers and hydration coefficient in the absence of biological inoculation, cattle manure and chemical fertilizers. On one hand, AM and Rhizobium inoculum showed the highest correlation (r = 0.97) between the nonsoaker percent and the total defect percent. On the other hand, the highest protein content was determined for Mycorrhiza and control treatments. Based on the results, Rhizobium and AM inoculation is a promising fertilizer because it is inexpensive, easy to handle and improves plant growth. Generally, microbial inoculation, organic and inorganic fertilizers not only increased plant growth and yield but also improved seed quality and nutritional value. The types of treatments used considerably enhanced the macro and micronutrients in the cultivar seed compared with the control.